Chest ultrasonography to assess the kinetics and efficacy of talc pleurodesis in a model of pneumothorax: an experimental animal study. Issue 2 (11th June 2018) - Tazi-Mezalek, Rachid; Frankel, Diane; Fortin, Marc; Kaspi, Elise; Guinde, Julien; Assolen, Alexandra; Laroumagne, Sophie; Robaglia, Andree; Dutau, Herve; Roll, Patrice; Astoul, Philippe
Talc pleurodesis is used to avoid recurrences in malignant pleural effusions or pneumothorax. The lack of lung sliding detected by chest ultrasonography (CUS) after talc application is indicative of the effectiveness of pleurodesis. The objective of our study was to explore, in an animal model, the capacity of CUS to predict the quality of a symphysis induced by talc poudrage (TP) and talc slurry (TS). We induced an artificial pneumothorax in six healthy pigs prior to talc application. TP was performed on one hemithorax, followed by TS on the other side 1 week later. 108 points on the chest were marked and evaluated by ultrasonography during the study. TP showed higher sonographic scores compared to TS starting from 72 h after talc administration. At autopsy, a higher grade of symphysis was observed for TP, and a high correlation rate was registered between CUS and macroscopic findings. Histological analysis also showed a higher grade of pleural symphysis for TP. CUS is a reliable tool to assess talc pleurodesis. The quality and kinetics of the pleural symphysis are also evaluable by ultrasonography. Pleurodesis by TP is more effective than TS in this experimental model of pneumothorax. Quality of talc pleurodesis and kinetics of pleural symphysis can be evaluated by chest ultrasonography http://ow.ly/8Ejt30jVTjn